Ethnobotanical study of antimalarial plants in the middle region of the Negro River, Amazonas, Brazil - Bernardo TOMCHINSKY; Lin Chau MING; Valdely Ferreira KINUPP; Ari de Freitas HIDALGO; Francisco Célio Maia CHAVES (Acta Amazonica, 2017)
ABSTRACT The middle Rio Negro region is an interesting place to seek novel antimalarial compounds because of the traditional knowledge of the Amazon population in conjunction with the high biodiversity of the region. The objective of this work was to study the use of antimalarial plants in Barcelos, state of Amazonas, Brazil. Fifty-two local specialists from eight different communities were interviewed over one year. The identified plants were collected with the assistance of local specialists, classified to species level and deposited in herbarium. In total, 55 antimalarial plants were identified in use in the region, of which 16 had not been previously reported in other published studies. Many factors could be involved with the use of antimalarial plants by the Barcelos population, such as the accessibility of these medicinal plants, efficiency and safety of using these plants, the accessibility to drugs or other medical treatments, plant bitterness, and the gender of the interviewees. Our results indicate that the population of Barcelos possesses an extensive knowledge on the use of a diverse array of antimalarial plants, and may contribute to the development of novel antimalarial compounds.